(untitled) (Global Journal of Medical Research, 2014)
Urinary schistosomiasis affects 200 million people worldwide it is a major source of morbidity and mortality in developing countries. Objectives: To compare the effectiveness of three diagnostic methods (urinalysis, ultrasound and cystoscopy) in evaluating the presence of S. haematobium infection. Material and Methods: This is a prospective crosssectional hospital based study conducted in three specialized urology centres in Khartoum, Sudan, in the period between Oct 2012-Sep 2012. It included all patients presenting to the outpatient clinics with different urinary tract symptoms and diagnosed as urinary schistosomiasis. Results: Dipstick tests showed haematuria (61.8%), while microscopy showed ova in only (3.1%) of patients. The majority of patients had no pathology on U/S exam (68%), minor pathology in (1%) and severe pathology in (31%) of patients.The most common ultrasound finding was increased bladder wall thickness (27.5%) followed by bladder masses (14.5%). Cystoscopy diagnosed the disease in all presenting patients; the most common cystoscopic findings were sandy patches (89.3%), followed by granuloma (23.7%). Conclusion: In this study cystoscopy was the most reliable investigation for diagnosing urinary schistosomiasis. Dipstick tests came second followed by ultrasonography, while urine for schistosomal ova was the least diagnostic test.